A fully assembled plastid‐encoded RNA polymerase complex detected in etioplasts and proplastids in Arabidopsis. Issue 3 (20th November 2020) - Ji, Yan; Lehotai, Nóra; Zan, Yanjun; Dubreuil, Carole; Díaz, Manuel Guinea; Strand, Åsa
Abstract: The plastid‐encoded genes of higher plants are transcribed by at least two types of RNA polymerases, the nuclear‐encoded RNA polymerase (NEP) and the plastid‐encoded RNA polymerase (PEP). In mature photosynthesizing leaves, the vast majority of the genes are transcribed by PEP. However, the regulatory mechanisms controlling plastid transcription during early light response is unclear. Chloroplast development is suggested to be associated with a shift in the usage of the primary RNA polymerase from NEP to PEP as the expression of the plastid‐encoded photosynthesis genes is induced upon light exposure. Assembly of the PEP complex has been suggested as a rate‐limiting step for full activation of plastid‐encoded photosynthesis gene expression. However, two sigma factor mutants, sig2 and sig6, with reduced PEP activity, showed significantly lower expression of the plastid‐encoded photosynthesis genes already in the dark and during the first hours of light exposure indicating that PEP activity is required for basal expression of plastid‐encoded photosynthesis genes in the dark and during early light response. Furthermore, in etioplasts and proplastids a fully assembled PEP complex was revealed on Blue Native PAGE. Our results indicate that a full assembly of the PEP complex is possible in the dark and that PEP drives basal transcriptional activity of plastid‐encoded photosynthesis genes in the dark. Assembly of the complex is most likely not a rate‐limiting step for full activation of plastid‐encoded photosynthesis gene expression which is rather achieved either by the abundance of the PEP complex or by some posttranslational regulation of the individual PEP components.